Beyond the Usual Suspects: Unraveling the Etiology of Abdominal Pain with Behcet’s Disease Intestinal Manifestation - Kurt, Idris; Kahveci, Abdulvahap (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Kurt I, Kahveci A. Beyond the usual suspects: Unraveling the etiology of abdominal pain with Behcet’s disease intestinal manifestation. Turk J Gastroenterol. 2024;35(10):808-810.